The role of social capital on culture preservation and organization transformation among new Chinese chambers of commerce members in Thailand - Jiafan Sheng; Yaoping Liu; Daranee Pimchangthong; Junaidi Junaidi (Problems and Perspectives in Management, 2025)
This study aims to examine the role of social capital dimensions (e.g., structural, relational, and cognitive) in influencing business transformation among new Chinese chambers of commerce in Thailand towards cultural preservation. A total of 525 members of the new Chinese chambers of commerce participated in Thailand. Structural equation modeling (SEM) was used to examine the research hypotheses. Structural social capital has a positive and significant effect on relational social capital and cognitive social capital. Cognitive social capital also has a positive and significant effect on relational social capital. Furthermore, social capital dimensions (e.g., structural, cognitive, and relational social capital) also have a positive and significant effect on business transformation directly and indirectly towards culture preservation. The findings advance both theoretical knowledge and practical applications, offering insights for businesses and policymakers seeking to leverage social capital for sustainable transformation and long-term success. Social capital dimensions can enhance innovation, facilitate organizational change, and promote flexibility in an increasingly complex and competitive business environment across cultures, industries, and organizational settings.